The course of my life my autobiography - Heath, Edward (Coronet Books, 1999)
Since joining the House of Commons in 1950, Edward Heath has been at the centre of British political life - as Chief Whip, Minister of Labour, Lord Privy Seal, Leader of the Conservative Party, and Prime Minister from 1970 to 1974. Here, writing with great candour, he offers us an entertaining insight into the events of the past sixty years.